1992
DOI: 10.2214/ajr.158.5.1566683
|View full text |Cite
|
Sign up to set email alerts
|

Crossed cerebellar diaschisis and crossed cerebellar atrophy: correlation of MR findings, clinical symptoms, and supratentorial diseases in 26 patients.

Abstract: symptoms and supratentorial disease. Of the 26 patients, eight had cerebellar atrophy; the remaining 18 patients showed no MR abnormality of the affected cerebellum. In the 18 in whom no atrophy was seen on MR imaging, the majority of the supratentorial lesions were tumors. The eight patients in whom cerebellar atrophy was demonstrated usually had significant contralateral supratentorial hemispheric atrophy. The patients with atrophy were also generally younger (average age, 14 years) than the 18 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
1
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 0 publications
2
99
1
4
Order By: Relevance
“…The phenomenon of diaschisis has been said to explain the development of CA in patients with epilepsy (18). Diaschisis is defined as a disturbance of function in one region of the brain, occurring as a result of a focal disturbance in a remote but anatomically connected region (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of diaschisis has been said to explain the development of CA in patients with epilepsy (18). Diaschisis is defined as a disturbance of function in one region of the brain, occurring as a result of a focal disturbance in a remote but anatomically connected region (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…CT and MRI can show a chronic infarct of MCA territory and atrophy of the contralateral hemicerebellum [33]. Confounding diagnosis in this case is reporting cerebellar hemiatrophy as an event, which is independent from the primary ischemic damage.…”
Section: Casementioning
confidence: 74%
“…The volume loss of the opposite cerebellar hemisphere could be at least in part explained by the phenomenon of crossed cerebellar diaschisis, in which functional disconnection of the cerebral cortex results in hypometabolism of the contralateral cerebellar hemisphere. Cerebellar volume loss is described in crossed cerebellar diaschisis 16 ; and Yoshikawa et al 17 reported a child with SWS in whom there was a reduction in the cerebral blood flow and metabolism in the cerebral cortex underlying the angioma and in the contralateral cerebellum. However, to our knowledge, folial pial enhancement has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the patient had increasing head circumference from infancy, plateauing at 4 years of age, and right glaucoma. MR images obtained at 6,16, and 45 months demonstrated fine vessels within the subarachnoid spaces bilaterally, progressive macrocrania, and enlargement of the right globe. MR venography used to supplement the final study confirmed patency of the dural venous sinuses and deep venous system with no clear abnormality of the superficial cortical venous system.…”
Section: Sws Without Pial Enhancementmentioning
confidence: 96%